2019
DOI: 10.1136/acupmed-2017-011615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electroacupuncture on anxiety and depression in unmarried patients with polycystic ovarian syndrome: secondary analysis of a pilot randomised controlled trial

Abstract: Objective: To evaluate the efficacy of electroacupuncture (EA) for the treatment of anxiety and depression in unmarried patients with polycystic ovarian syndrome (PCOS) by secondary analysis of a randomised controlled trial. Methods: A prospective pilot randomised controlled trial of unmarried women with PCOS was conducted from November 2012 to March 2016. Participants were assigned to the acupuncture group (receiving EA for 16 weeks) or the control group (receiving sham acupuncture for 16 weeks), with 27 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
1
24
0
1
Order By: Relevance
“…Previous studies have demonstrated that deficiency of monoamine neurotransmitters, such as serotonin, noradrenaline, and dopamine, in the central and peripheral nervous system is a major cause of depression [20,44]. The changes in the serum levels of monoamine neurotransmitters and their metabolites can be used as important biomarkers for diagnosis of depression [17,18]. In the current study, we explored the possible changes in the serum serotonin and norepinephrine concentrations when dezocine was intravenously administered during PCIA.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that deficiency of monoamine neurotransmitters, such as serotonin, noradrenaline, and dopamine, in the central and peripheral nervous system is a major cause of depression [20,44]. The changes in the serum levels of monoamine neurotransmitters and their metabolites can be used as important biomarkers for diagnosis of depression [17,18]. In the current study, we explored the possible changes in the serum serotonin and norepinephrine concentrations when dezocine was intravenously administered during PCIA.…”
Section: Plos Onementioning
confidence: 99%
“…In particular, serotonin and norepinephrine reuptake inhibitors are firstline antidepressant drugs. Moreover, several previous studies have reported that increased serum concentrations of norepinephrine and serotonin were associated with improved depressive symptoms [17][18][19][20][21]. Furthermore, a recent study found that postoperative patient-controlled intravenous analgesia (PCIA) using tramadol, which has serotonin and norepinephrine reuptake inhibitory effects, can significantly decrease the postoperative depression scores [22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have mainly focused on the analgesic effect of EA (Zhang et al, 2014). However, multiple studies found that EA not only has neuromodulatory effects (Liu Z. et al, 2017;Chen et al, 2018), but can also ameliorate the symptoms of several neuropsychiatric diseases, such as the cognitive impairment in Alzheimer's and Parkinson's disease, and anxiety and depression in unmarried patients with polycystic ovarian syndrome (Li et al, 2019;Tamtaji et al, 2019;Wang et al, 2019;Zheng et al, 2021). Interestingly, a large number of studies reported that EA exerts neuroprotective effects by regulating the structure and function of the hippocampus and PFC (He et al, 2018;Chen et al, 2019;Marcus et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…9,11 Electroacupuncture (EA) has been used to treat a wide variety of medical conditions, such as knee osteoarthritis, 12 stress urinary incontinence, 13 functional constipation, 14 and so on. Recently, EA has been demonstrated to have beneficial effects on neuropsychiatric disorders, [15][16][17][18] including PSD. 19 Animal studies showed that hippocampal sonic hedgehogsignaling pathway, 20 Keap1/Nrf2 antioxidant signaling pathway, 21 and endocannabinoid signaling pathway 22 may be involved in the protective mechanism of EA on PSD.…”
Section: Introductionmentioning
confidence: 99%